Correlation between anthropometric measurements and graft size in anterior cruciate ligament reconstruction: a systematic review and meta-analysis - Loay A. Salman (14150322) (2023)
Purpose This systematic review and meta-analysis aimed to investigate the correlation between anthropometric measurements and graft size in anterior cruciate ligament (ACL) reconstruction. Methods A systematic search of Ovid MEDLINE, Embase, and Cochrane Library databases was conducted for observational studies published until March 2023 that reported the relationship between anthropometric data [height, weight, body mass index (BMI), age, gender, thigh length, and circumference] and ACL graft size. Correlation coefficients (COR) and their associated 95% confidence intervals were used as the primary effect size. This review was conducted in line with PRISMA guidelines. Results A total of 42 observational studies involving 7110 patients were included, with a mean age of 29.8 years. Statistically significant, moderately positive correlations were found between graft size and height (COR: 0.49; 95% CI: 0.41–0.57; p-value: < 0.001), weight (COR: 0.38; 95% CI: 0.31–0.44; p-value: < 0.001), thigh circumference (COR: 0.40; 95% CI: 0.19–0.58; p-value: < 0.001), and thigh length (COR: 0.35; 95% CI: 0.18–0.50; p-value: < 0.001). However, age and gender were insignificantly correlated with graft size (p-value: NS). A subanalysis based on graft type showed a significant positive correlation between height and graft diameter, which was more significant in the peroneus tendon than in hamstring grafts (COR: 0.76 vs. 0.45; p-value: 0.020). Conclusion This study demonstrated a moderate positive correlation between anthropometric measurements (height, weight, thigh circumference, and length) and ACL graft size, along with a weak positive correlation with BMI. Age and gender showed no significant correlation. These findings support the predictability and selection of ACL graft size based on pre-operative patient anthropometric data. Level of evidence Level of Evidence: IV. PROSPERO registration number: CRD42023416044. Other Information Published in: European Journal of Orthopaedic Surgery & Traumatology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00590-023-03712-w